2019 IEEE/CVF International Conference on Computer Vision (ICCV) 2019
DOI: 10.1109/iccv.2019.00231
|View full text |Cite
|
Sign up to set email alerts
|

GP2C: Geometric Projection Parameter Consensus for Joint 3D Pose and Focal Length Estimation in the Wild

Abstract: We present a joint 3D pose and focal length estimation approach for object categories in the wild. In contrast to previous methods that predict 3D poses independently of the focal length or assume a constant focal length, we explicitly estimate and integrate the focal length into the 3D pose estimation. For this purpose, we combine deep learning techniques and geometric algorithms in a two-stage approach: First, we estimate an initial focal length and establish 2D-3D correspondences from a single RGB image usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…While instancelevel 3D object pose estimation has long been studied in both robotic and vision communities [19,1,21,42,48,43,60,47,37,24], class-level pose estimation has developed more recently thanks to learning-based methods [45,52,51,34,23,55,14,13,56,66,50]. These methods can be roughly divided into two categories: direct pose estimation methods that regress 3D orientations directly [52,45,34,55,63], and keypoint-based methods that predict 2D locations of 3D keypoints [14,13,56,66,50]. However, annotating 3D poses for objects in the wild is a tedious process of searching best-matching CAD models and aligning them to images [59,58].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…While instancelevel 3D object pose estimation has long been studied in both robotic and vision communities [19,1,21,42,48,43,60,47,37,24], class-level pose estimation has developed more recently thanks to learning-based methods [45,52,51,34,23,55,14,13,56,66,50]. These methods can be roughly divided into two categories: direct pose estimation methods that regress 3D orientations directly [52,45,34,55,63], and keypoint-based methods that predict 2D locations of 3D keypoints [14,13,56,66,50]. However, annotating 3D poses for objects in the wild is a tedious process of searching best-matching CAD models and aligning them to images [59,58].…”
Section: Related Workmentioning
confidence: 99%
“…Object Detection on Pix3D. Results are given in AccD 0.5 as defined in [13]. We compare with two methods [55,13] that train a class-specific Mask R-CNN on COCO, then fine-tune on a subset of Pix3D containing the same classes as COCO.…”
Section: Class-agnostic Object Detection and Pose Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection and tracking in 3D space from video sequences is a relatively unexplored area due to the difficulty in the 6-DoF (six degrees of freedom) pose estimation. In order to accurately estimate 3D positions and poses, many methods [13,23] leverages a predefined object template or priors to jointly infer object depth and rotations. In ClusterVO, the combination of low-level geometric feature descriptors and semantic detections inferred simultaneously in the localization and mapping process can provide additional cues for efficient tracking and accurate object pose estimation.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, it is important to know which pixels belong to an object and which pixels belong to the background or another object [7,8]. Recent works showed that deep learning techniques for instance segmentation [17] significantly increase the accuracy on this task [15,26,59]. However, until now location fields have only been used for 3D pose estimation, but not for 3D model retrieval or other tasks.…”
Section: Location Fieldsmentioning
confidence: 99%